PhD students' experiences of thesis supervision in Malaysia: managing relationships in the midst of institutional change - Krauss, Steven Eric; Ismail, Ismi Arif (Nova Southeastern University, 2010)
Despite the plethora of studies that have been conducted on PhD supervision, little qualitative investigation has been conducted with a diverse, non-Western sample of doctoral students in an attempt to understand how the supervisory relationship is experienced. In response, eighteen students from diverse, non-Western backgrounds studying at one Malaysian research university were interviewed. Results illuminated the theme of "management" of the supervisory experience and included two streams:(a) acceptance of the situation, and (b) response to the situation so as to optimize their experience. The two major themes further included four sub-themes that included managing personal relations, time and accessibility constraints, academic compatibility, and expectations. Implications for the development of international research universities where PhD supervision of a diverse student body is a critical factor for university success and development are discussed.